Preparedness and response to COVID-19 in a quaternary intensive care unit in Australia: perspectives and insights from frontline critical care clinicians. Issue 2 (4th February 2022) - Sundararajan, Krishnaswamy; Bi, Peng; Milazzo, Adriana; Poole, Alexis; Reddi, Benjamin; Mahmood, Mohammad Afzal
Abstract : Objectives: This study was conducted to explore the perspectives and opinions of intensive care unit (ICU) nurses and doctors at a COVID-19-designated pandemic hospital concerning the preparedness and response to COVID-19 and to consolidate the lessons learnt for crisis/disaster management in the future. Design: A qualitative study using in-depth interviews (IDIs) and focus group discussions (FGDs). Purposeful sampling was conducted to identify participants. A semistructured guide was used to facilitate IDIs with individual participants. Two FGDs were conducted, one with the ICU doctors and another with the ICU nurses. Thematic analysis identified themes and subthemes informing about the level of preparedness, response measures, processes, and factors that were either facilitators or those that triggered challenges. Setting: ICU in a quaternary referral centre affiliated to a university teaching COVID-19-designated pandemic hospital, in Adelaide, South Australia. Participants: The participants included eight ICU doctors and eight ICU nurses for the IDIs. Another 16 clinicians participated in FGDs. Results: The study identified six themes relevant to preparedness for, and responses to, COVID-19. The themes included: (1) staff competence and planning, (2) information transfer and communication, (3) education and skills for the safe use of personal protective equipment, (4) team dynamics and clinical practice, (5) leadership, and (6) managing end-of-life situations and expectations of caregivers. Conclusion: Findings highlight that preparedness and response to the COVID-19 crisis were proportionate to the situation's gravity. More enablers than barriers were identified. However, opportunities for improvement were recognised in the domains of planning, logistics, self-sufficiency with equipment, operational and strategic oversight, communication and managing end-of-life care.